2020
DOI: 10.5614/crbb.2019.1.2/onxn6178
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and cytotoxicity property of extracts from various coastal plants against HepG2 cell lines

Abstract: Reports have shown an upward trend for liver cancer in recent years. It is also one of the deadliest cancers globally due to its complexity in detection and treatment. Hence, there is an urgency to develop the anti-liver cancer agent from natural resources which is highly effective with minimum side effects. This study aimed to evaluate the antioxidant activity and cytotoxicity property of extracts with different polarity solvents (hexane and methanol) obtained from coastal plants collected from Merang, Tereng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…These cells are sensitive to cytotoxic effects and are therefore widely used in test systems in original studies of promising pharmacological drugs [ 48 ]. When studying the systemic metabolism of drugs, cell lines of hepatocyte origin are used, such as the HepG2 cell line [ 49 , 50 , 51 ], which we used to determine the possible risks of the applied combination of ascorbic acid and lysozyme hydrochloride on SH-groups, TBA-active components, and catalase activity as important indicators of antioxidant protection. MAEC line was used as a model system that plays an important role in the endothelial barrier of drug permeability [ 52 , 53 ] to determine possible changes in the morphofunctional features of these cells under the action of ascorbic acid and lysozyme hydrochloride.…”
Section: Resultsmentioning
confidence: 99%
“…These cells are sensitive to cytotoxic effects and are therefore widely used in test systems in original studies of promising pharmacological drugs [ 48 ]. When studying the systemic metabolism of drugs, cell lines of hepatocyte origin are used, such as the HepG2 cell line [ 49 , 50 , 51 ], which we used to determine the possible risks of the applied combination of ascorbic acid and lysozyme hydrochloride on SH-groups, TBA-active components, and catalase activity as important indicators of antioxidant protection. MAEC line was used as a model system that plays an important role in the endothelial barrier of drug permeability [ 52 , 53 ] to determine possible changes in the morphofunctional features of these cells under the action of ascorbic acid and lysozyme hydrochloride.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, it was found that the result of anticancer activity of the methanolic extract of the stem bark of Senna alata (Gelenggang) varied between previous studies due to different types of cancer cell lines used by both studies: MCF-7 breast cancer cells and PC-3 prostate cancer cell lines which then resulting in two different cytotoxic effects which are moderate and weak with IC 50 values at 47.11 µg/mL and 427.77 µg/mL, respectively (Madankumar et al, 2020;Kamarudin et al, 2021). Another study also reported that the different anticancer activity of ethanolic extract of Morinda citrifolia (Mengkudu) fruit on different cancer cell lines: THP-1 human monocyte cell and MDA-MB-231 breast cancer cell line resulting in different IC 50 values at 0.39 µg/mL (highly active) and 49.72 µg/mL (moderately active), respectively (Tsao et al, 2020;Vyn et al, 2020). Based on these results, it can be concluded that the same extract used on the different cancer cell lines might produce different results.…”
Section: Anticancer Activity Of Malaysian Medicinal Plants (In Vitro)mentioning
confidence: 99%